Hamlet, Prince of Denmark. - Shakespeare, William, 1564-1616 (First Avenue Classics Ser., 2014)
"Something is rotten in the state of Denmark." Brooding Hamlet, the son of the recently deceased king, is about to discover the royal family's corruption firsthand. Taken by the castle watchman to meet the apparition they see at night, Hamlet is surprised to find it is his father's ghost. Hamlet seeks to avenge his father's dishonorable death, but the casualties along the way may prove to be just as tragic. Enter William Shakespeare's famous world of betrayal, madness, and "murder most foul" through this unabridged version of Hamlet, Prince of Denmark, first published in England in 1603.